Radial structure of low pressure rf capacitive discharges - Lisovskiy, V.; Kharchenko, N.; Yegorenkov, V. (journal homepage: www.elsevier.com/locate/vacuum, 2010)
This paper studies the glow intensity distribution of the discharge plasma against the tube radius and reports the radial profiles of electron temperature and plasma concentration in the rf capacitive discharge registered with a Langmuir probe. An abrupt increase of electron temperature and glow intensity near the tube wall in the weak-current a-mode of the rf capacitive discharge is revealed, the radial distribution of plasma concentration and ion flow to the electrodes possessing a maximum near the radial sheath boundary. In the g-mode of the rf capacitive discharge the electron temperature decrease in the total plasma volume leads to an electric field weakening and the peak of the glow intensity near the tube wall vanishes. The radial sheath thickness in the a-mode of the rf capacitive discharge obtained with 2D simulation experiences pulsations during the rf field period, the changing radial electric field heating electrons and increasing the plasma concentration near the boundary of the radial sheath.
Keywords: plasma physics; gas discharges